Overview of options for generating high-brightness attosecond x-ray pulses at free-electron lasers and applications at the European XFEL. (9th January 2018) - Serkez, S; Geloni, G; Tomin, S; Feng, G; Gryzlova, E V; Grum-Grzhimailo, A N; Meyer, M
Abstract: The generation of attosecond, highbrightness x-ray pulses is a matter of great interest given their applications in the study of ultra-fast processes. In recent years, the production of x-ray pulses of high brightness, both in the soft and in the hard x-ray range, has been enabled by x-ray free-electron lasers (XFELs). In contrast to conventional quantum lasers, XFELs are based on the use of an ultra-relativistic electron beam as gain medium. They often work in the self-amplified spontaneous emission (SASE) regime, which provides pulses of duration down to a few femtoseconds, composed of several longitudinal modes. In order to further decrease the duration of these pulses, special methods need to be implemented. In this paper we review available methods, with particular focus on the x-ray laser-enhanced attosecond pulse generation, which is one of the most promising techniques. We illustrate the method using the SASE3 soft x-ray undulator of the European XFEL facility as a case study, emphasizing the importance of high-repetition rate attosecond x-ray pulses. The expected attosecond-level radiation output is used for simulations of sequential ionization processes in atoms in the case of ionization in the soft x-ray regime, demonstrating the importance of this opportunity for the user community.